Female Civil Servants as Second Wives: Ethical Governance, Gender Equality, and Merit-Based Human Resource Management in Indonesia’s Civil Service - Endah Wal Istanawati; Aprianti Yofita Rahayu (Blantika: Multidisciplinary Journal, 2026)
The status of female civil servants (Aparatur Sipil Negara/ASN) as second wives is commonly framed as a moral or marital law issue. Within bureaucratic practice, however, this phenomenon has significant implications for public human resource management and ethical governance. This study examines the implications of the marital status of female ASN as second wives within Indonesia’s civil service management system and formulates policy recommendations aligned with merit-based principles, public ethics, and gender equality. Employing a qualitative descriptive method with a deductive and socio-legal approach, this study analyzes primary legal materials governing civil service management, discipline, ethics, and marriage, complemented by relevant academic literature. The findings reveal a regulatory gap in civil service law, as existing regulations do not explicitly govern the status of female ASN who become second wives. This gap has led to inconsistent administrative interpretations and potential gender-based discrimination in performance evaluation and career development. The study concludes that the issue constitutes a public human resource management and policy challenge rather than merely an individual moral concern, underscoring the need for explicit, proportional, and gender-sensitive governance frameworks in ASN management.